Evidence for Human Streptococcus pneumoniae in wild and captive chimpanzees: A potential threat to wild populations. Issue 1 (December 2017) - Köndgen, Sophie; Calvignac-Spencer, Sebastien; Grützmacher, Kim; Keil, Verena; Mätz-Rensing, Kerstin; Nowak, Kathrin; Metzger, Sonja; Kiyang, John; Becker, Antina; Deschner, Tobias; Wittig, Roman; Lankester, Felix; et al.
Abstract Habituation of wild great apes for tourism and research has had a significant positive effect on the conservation of these species. However, risks associated with such activities have been identified, specifically the transmission of human respiratory viruses to wild great apes, causing high morbidity and, occasionally, mortality. Here, we investigate the source of bacterial-viral co-infections in wild and captive chimpanzee communities in the course of several respiratory disease outbreaks. Molecular analyses showed that human respiratory syncytial viruses (HRSV) and human metapneumoviruses (HMPV) were involved in the etiology of the disease. In addition our analysis provide evidence for coinfection withStreptococcus (S.) pneumoniae . Characterisation of isolates from wild chimpanzees point towards a human origin of these bacteria. Transmission of these bacteria is of concern because – in contrast to HRSV and HMPV -S. pneumoniae can become part of the nasopharyngeal flora, contributing to the severity of respiratory disease progression. Furthermore these bacteria have the potential to spread to other individuals in the community and ultimately into the population. Targeted vaccination programs could be used to vaccinate habituated great apes but also human populations around great ape habitats, bringing health benefits to both humans and wild great apes.